Acinar Cell Proliferation Promoted by BMP2 in Injured Mouse Parotid Gland: BMP2 Promotes Cell Proliferation in Parotid Gland - Megumi Yokoyama; Osamu Katsumata-Kato; Junko Fujita-Yoshigaki (Hindawi Limited, 2023)
Objective. To identify factors that affect salivary gland recovery, we investigated the expression and function of bone morphogenetic protein 2 (BMP2) in mice. Materials and Methods. Using a micro clip, mice parotid glands were removed 7 days after the ligation of the unilateral parotid excretory duct. Thereafter, they were weighed and stained with hematoxylin and eosin, and BMP2 expression was examined via real-time reverse transcription-polymerase chain reaction. Primary cultures of parotid glands were prepared, and BMP2 protein was added to the culture medium for 48 hr to examine its effect on cell proliferation. E-cadherin and vimentin expression was examined using western blotting. Finally, immunohistochemical staining using an anti-Ki67 antibody was performed. Results. Duct-ligated parotid glands weighed less than those that were collected after sham surgery and showed acinar cell atrophy. They also showed higher BMP2 expression than control glands. Primary-cultured parotid acinar cells supplemented with BMP2 showed higher proliferative potential than control cells. Furthermore, they showed E-cadherin, but not vimentin, expression, and their percentage of Ki67-positive cells were higher than that corresponding to the controls. Conclusions. Injury to salivary glands by excretory duct ligation increased BMP2 expression, which may be involved in maintaining salivary gland function by inducing acinar cell proliferation.